Public value perspectives of Integrated Development Planning in Thulamela Local Municipality - Mudau, Ndivhudza (My University, 2023)
Integrated development planning has changed the way in which community and local government interact about service delivery. This study was based on the public value perspective of Integrated Development Planning (IDP). The IDP commits that municipalities must work with communities in ensuring that together sustainable ways to improve the value of lives of all citizens can be reached. The South African government has adopted development approach for local government to eradicate the legacy of apartheid. The local government has developed and formulated policies to promote and strengthen development planning in municipalities. The Municipal System Act, 2000 (Act 32 of 2000), Section 118 mandated that municipality should provide principles and mechanism that will enable municipality to move progressively towards social and economic upliftment of local communities. However, several studies have indicated that there is lack of community participation in the process of IDP. The nature of IDP should be understood on the perspective of public value creation. This study adopted positivist method. The study adopted a descriptive research design. A probability sampling was used in the study and the cluster sampling approach was adopted to select the sample of which the sample size was selected from employees of Thulamela Local Municipality and community representatives. Structured questionnaire was used to gather information. A descriptive statistic was used to analyze data. The researcher followed research ethics before conducting the study. The study found that there is too much control from the three levels of government which frustrates the process of democracy. The study showed that most public participations are not inclusive and are not involved on deliberation and creating new understandings but rather are oriented to consulting with the public to gather input or just allowing people to express different perspectives. The researcher revealed that the roles of the other sphere of government are not clear in the local developments. The study findings showed that local authorities are not equipped to undertake the developmental role envisaged in the IDP. The findings showed that traditional role of local government is non consultative and paternalistic. The study found that local authorities lack the capability to coordinate multiple stakeholders in development initiatives. The findings of the study revealed that operating as equal partners with national and provincial government agencies at the local level makes it difficult to operate. The study recommended that there should not be too much control from the three levels of government to strengthen the process of democracy. The recommendations of the study noted that public participation should be inclusive and involved in deliberation and creating new understandings and oriented to consulting with the public to gather input for people to express different perspectives. The researcher recommends that the roles of the other sphere of government should be clear in the local developments. The Recommendations of the study showed that local authorities should be equipped to undertake the developmental role envisaged in the IDP. The recommendations of the study showed that traditional role of local government should be non-consultative and paternalistic. The study recommends that local authorities should have the capability to coordinate multiple stakeholders in development initiatives. According to the findings, the study recommends that operating as equal partners with national and provincial government agencies at the local level should not be difficult to operate. According to the study, the IDP process of Municipalities should be clear and there should be opportunity for all to participate and contribute to the IDP process. The study recommended that Municipality should regularly use participatory focus groups during the IDP process.
MAdmin
Department of Public and Development Administration
Keywords: Integrated Development Planning; UCTD; Service delivery; Community participation; Local government; Public value; 354.27930968257; Community development -- South Africa -- Limpopo; Rural development -- South Africa -- Limpopo; Economic development projects -- South Africa -- Limpopo; Civil society -- South Africa --Limpopo; Local development -- South Africa -- Limpopo; Municipal government -- South Africa -- Limpopo; Rural development -- South Africa -- Limpopo